Assessment of contraceptive utilization and associated factors among sexually active HIV-positive Indian women: A cross-sectional study from an antiretroviral therapy center - Sneha Sagar; Aamir Bashir; Biplab Pal; Mukhtar Ahmad Dar; Krishna Pandey; Krishna Murti (Elsevier, 2021)
Background: HIV/AIDS epidemic is one of the most serious global public health problems, more particularly seen in low and middle-income countries. Females contribute around 40% of total HIV cases in India who predominantly belong to fertile age group. This study aimed to assess the contraceptive utilization patterns and factors affecting the HIV-positive Indian women. Methods: A cross-section of 400 confirmed HIV-positive women aged between 18 and 45 years were recruited. All the relevant information including socio-demographic and anthropometric details were collected from the participants. All other needed parameters were recorded from patients file. The SPSS ver. 21 was used to perform statistical analysis. Results: The mean age of the participants was found to be 29.53 ± 5.35 years. The majority of women were housewives (97%), Illiterate (58.8%) and 90.5% had a monthly family income under 10,000 INR. Maximum (82.8%) of HIV transmission was found through unprotected sexual routes while 68.8% of patients were on HAART. Male condoms were highly utilized whereas 44.3% of participants never used any methods. Percentage of consistent contraceptive use was highest when patients were educated to graduate level (66.7%), aware of contraception methods (49.8%) and who have a monthly income more than 20,000 INR (66.7%). Conclusion: This study gives a real picture of the contraceptive utilization among HIV-infected women from rural regions of India. The study anticipates the immediate needs in healthcare sector to improve awareness of patients regarding modern methods of contraception and effective family planning strategies.